2021
DOI: 10.5334/bc.108
|View full text |Cite
|
Sign up to set email alerts
|

Dhaka landfill waste practices: addressing urban pollution and health hazards

Abstract: Two Dhaka, Bangladesh, landfills are explored to understand how management practices impact environmental quality and public health in the surrounding areas. A combination of research methods is used, such as geospatial buffer zone analysis, semi-structured observation checklist and qualitative interviews, to gain an understanding of the waste transportation, leachate percolation, and adverse health and environmental effects. A multi-ring buffer zone and ground truth method were applied through ArcMap for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…68 A recent observation from the nearby villages of the Amin Bazar landfill revealed that the surrounding surface waterbodies have become unsuitable for fish cultivation, forcing the farmers and fishermen in these areas to switch livelihoods. 69 The treated Rajbandh landfill leachate contains high concentrations of trace metals and other toxic substances and is unsuitable to be discharged into inland waters. 44 Thus, improving the existing leachate treatment units and establishing new units and are essential, considering the shortcomings of the current treatments.…”
Section: Treatment Challenges and Pollutionmentioning
confidence: 99%
“…68 A recent observation from the nearby villages of the Amin Bazar landfill revealed that the surrounding surface waterbodies have become unsuitable for fish cultivation, forcing the farmers and fishermen in these areas to switch livelihoods. 69 The treated Rajbandh landfill leachate contains high concentrations of trace metals and other toxic substances and is unsuitable to be discharged into inland waters. 44 Thus, improving the existing leachate treatment units and establishing new units and are essential, considering the shortcomings of the current treatments.…”
Section: Treatment Challenges and Pollutionmentioning
confidence: 99%
“…During the tour, the researcher engaged the inhabitants in an unstructured interview to establish the nature of the land ll's impact on the neighborhood. However, according to the previous studies, people residing within the proximity of 500m -2 km from the land ll sites are severely affected (De and Debnath 2016;Ganesan 2017;Urme et al 2021;Singh et al 2021). As a result, two techniques, namely purposive and criteria sampling procedures, were used to collect the data for the present study.…”
Section: Materials and Methodologymentioning
confidence: 97%
“…Subsequently, the nal interviews were done using a semi-structured questionnaire (includes both open and close-ended questions), which allowed respondents to express a wide range of opinions on how the dumpsite has impacted their lives. Besides, quantitative techniques like site observation, focus group discussion, and note on perceptions were also adopted to understand better their real-life scenarios and adjustments near the land ll sites (De and Debnath 2016;Weldeyohanis 2020;Urme et al 2021;Etea et al 2021). However, all these data were collected with the help of some enumerators after proper instruction and preparation.…”
Section: Formulating Questionnaire Design and Data Collection Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Although some catalytic and purification equipment is usually installed in motor vehicles, sulfur dioxide usually accumulates on its surface, which makes the use of catalytic equipment inconvenient [6][7]. With the rapid development of industrial desulfurization technology, the sulfur dioxide produced by vehicle exhaust will be greatly reduced, but the pollution situation has not disappeared [8].…”
Section: Types and Hazards Of Automobile Exhaust Pollutionmentioning
confidence: 99%